Graphical user interface development for windows scripting - Olczyk, Krzysztof; Marańda, Witold (Oficyna Wydawnicza Politechniki Wrocławskiej, 2009)
Background: The computer software engineering market provides the developers with the multitude of various solutions: programming languages, platforms and frameworks to choose among. For automation of operating system administrative tasks (e.g. file manipulation, gluing applications, quick prototyping) the common choice is usually a scripting language (e.g. Bash, Perl, Tel, JScript) Motivation: It was identified that the standard Windows Script Host (WSH) for Microsoft Windows lacks a standardized and satisfactory technology for featuring its scripts with the functional graphical user interface. This recognition of the gap in Windows scripting led to the idea of providing the means of easy and robust definition of graphical user interface for scripting tasks in Windows environment (JScript / VBScript). Project: The aforesaid investigation led to the creation of the language/framework which provides the developers, experienced in windows scripting, with a tool to create standalone applications in the manner similar to creating desktop widgets or web pages. The description of an application user interface with the proposed language consist of an XML file binding script actions with tags corresponding to window control widgets from .NET Windows Forms library.
Keywords: scripting languages; graphical user interface; XML; compiler services; dynamic assembly generation; języki skryptowe; graficzny interfejs użytkownika; dynamiczne generowanie zasobów